From unpaid to paid care work: the macroeconomic implications of HIV and AIDS on women's time-tax burdens - Rania Antonopoulos; Taun N. Toay (Levy Economics Institute of Bard College, 2009)
This paper considers public employment guarantee programs in the context of South Africa as a means to address the nexus of poverty, unemployment, and unpaid work burdensall factors exacerbated by HIV/AIDS. It further discusses the need for genderinformed public job creation in areas that mitigate the time-tax burdens of women, and examines a South African initiative to address social sector service delivery deficits within the government's Expanded Public Works Programme. The authors highlight the need for well-designed employment guarantee programsspecifically, programs centered on community and home-based careas a potential way to help offset the destabilizing effects of HIV/AIDS and endemic poverty. The paper concludes with results from macroeconomic simulations of such a program, using a social accounting matrix framework, and sets out implications for both participants and policymakers.
Keywords: B54; E24; H51; I30; J16; J22; O55; 330; HIV/AIDS; gender; care work; unpaid work; Community and Homebased Care (CHBC); South Africa; Expanded Public Works Programme (EPWP); Social Accounting Matrix (SAM); employment guarantee